The concept and conditions for the creation of the Poznań Metropolitan Railway, taking into account economic, spatial and demographic aspects - Adam Pawlik (Przegląd Komunikacyjny)
Abstract: This article discusses the conditions for creating the Poznań Metropolitan Railway as an initiative by the authorities of the Wielkopolska Province, railway operators, and social organizations. This initiative responds to the transportation needs of residents in the Poznań Metropolitan Area (POM). The goal of the Poznań Metropolitan Railway is to improve the quality of passenger transport in the Poznań agglomeration (hereafter referred to as the Agglomeration) by developing an attractive and efficient network of railway connections within the existing framework of railway transport operations in Poland—significantly cheaper than providing a similar level of transport service by expanding the road network.